(untitled) (GYMNASIUM, 2009)
Clinical picture of the hand is complex rheumatoid impaired at multiple osteo-articular, muscle, tendons, ligaments. Lesions at the punch: tenosinovita extensorilor, sinovita radio-carpal, sidrom head cubits, sidrom carpal canal, redoarea punches, especially in the flex, mainly under the action of flexorilor initially subluxaţie web subsequently associated with radial deviation of pumnului.Leziuni at the fingers: a finger deviatţa cubits. fingers "thrown in the pen, fingers in buttonhole, policele" in Z "tenosinovitele hand. clinico assessment - functional recovery oriented program, outlines the methodology appropriate to each case, the clinical obiectiveaza obtained by certain procedures, focused on prognosticului.(1)Treatamentof the hand reumatoide. Objectives: preserving functional capacity of the rheumatoid hand, primarily from an articular musculoskeletal, functional capacity preserving outstanding (for each stage of the disease), adjusting activities according to current restantul functional real functional autonomy by maintaining maximum operating capacity remaining real(1). Kinetoterapie - Objectives: prevent deformation and vicious attitudes, maintain or increase joint mobility, increase strength and muscle rezisteţei, kinetic treatment should be early, continuous, permanent, adapted evolutionary stage of each patient, the type of deformation adapted existing adapted restantului actual running phase, adapted functional objectives of the needs subiectului.Ergoterapie.(2)